The yield and composition of milk and preweaning growth rate of Red Sokoto goats in Nigeria - Ehoche, O.W; Buvanendran, V. (1983)
A study was conducted at the national Animal Production Research Institute, Shika in northern Nigeria, to determine the milk yield and composition of the Red Sokoto goats and factors influencing it and the relationship between milk yield and kid weight gain. Each of the 26 Red Sokoto does, 15 nursing single kids and 11 nursing twin kids, were kept in a separate pen and fed mixed hay and 0.5kg per day of concentrate mixture. Milk yield was measured at weekly interval, from approximately 1 week after parturition till the 12-week of lactation, and injection of 5 I.U. of Oxytocin was used to stimulate milk let down. Kid weights were recorded at birth and on the days that milking was done. The data was analyzed by least square procedures and simple regression analysis. Daily milk yield reached a peak in the second week and then declined gradually to the end of lactation. Over the entire lactation, does with twin kids exceeded the milk production of does with single kids by about 20%. The influence of year, age of dam and type of birth on cumulative milk yields to 2, 4, 8 and 12 weeks of lactation showed that only the effects of type of birth reached significance for 2-week yields. None of the other effects was significant and all the variables accounted for only 10-30% of the variation in milk yield. Addition of dam weight as a covariate to the model, however, increased the variation explained to 36-61% and its effect was significant. There was evidence of significant stage of lactation effect on fat % (P